Numerical Study on Seepage of Chemical Grout Flow in Rock Fracture under Temperature Field. (9th May 2022) - Zhang, Qi; Zhang, Chenhao; Lin, Yifeng; Li, Yuanhai; He, Lei
Abstract : Grouting technology is widely used to improve the mechanical properties and reduce the permeability of the rock in underground engineering. Fluidity is important to promote the grout to be injected into longer fractures, so chemical grouts with low viscosity and adjustable gel time are usually chosen to increase this property. However, the high temperature in some deep engineering leads to a faster hydration rate of the chemical grout than that in the room temperature environment, resulting in the decrease of fluidity. The heat exchange between the grout and the environment is usually ignored in the existing researches, so the aim of the numerical study is therefore to analyse the seepage process of chemical grout in the temperature field, where heat exchange between the grout and environment is considered. A sandstone model with a fracture is established in COMSOL, which is validated using laboratory experiments to confirm the accuracy of the results. The grouting time rises exponentially with the increasing of the flow distance in a single fracture, and a higher environmental temperature leads to a larger grouting time because the gap in the viscosity of the grout at different temperatures enlarges with the increasing hydration time. The effect of the temperature field on the grouting time becomes more significant when the temperature is higher and the hydration time is longer because the viscosity of the grout rises more slowly. The grouting time reduces dramatically when injection pressure is raised because an increasing pressure results in a larger aperture and less hydration time, which is one of the best ways to improve the efficiency of the grouting. The findings of this study can help for better understanding of the seepage process of chemical grout in fractures under high temperature and provide guidance for the selection of chemical grout in grouting engineering.